2016
DOI: 10.11138/ccmbm/2016.13.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Abaloparatide

Abstract: SummaryAbaloparatide is an investigational analog of human PTHrP (1-34) being developed for the treatment of osteoporosis. The amino-acid sequence of abaloparatide is identical to that of PTHrP in the first 20 amino-acids, while over half of the remaining amino-acids are different. Some studies in animals and in humans reported that abaloparatide presented a potent anabolic activity with reduced effects on bone resorption as compared to that observed with teriparatide. This may be due to a more transient signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
9
0
3
Order By: Relevance
“…Abaloparatide (ABL), a new drug for osteoporosis, is identical to PTHrP through the first 22 residues but, thereafter, several substituent amino acids render this molecule very different in terms of its interactions at the receptor level . Both TPTD and ABL act on the same receptor but in different ways . The difference in activity between the two molecules may be explained, at least in part, by the way in which these two peptides interact at the two conformational configurations of the PTHR1 receptor, namely R0 and RG .…”
Section: Pth and Pthrp Analoguesmentioning
confidence: 99%
“…Abaloparatide (ABL), a new drug for osteoporosis, is identical to PTHrP through the first 22 residues but, thereafter, several substituent amino acids render this molecule very different in terms of its interactions at the receptor level . Both TPTD and ABL act on the same receptor but in different ways . The difference in activity between the two molecules may be explained, at least in part, by the way in which these two peptides interact at the two conformational configurations of the PTHR1 receptor, namely R0 and RG .…”
Section: Pth and Pthrp Analoguesmentioning
confidence: 99%
“…Such approaches have already proven beneficial for the treatment of osteoporosis, such as the development and FDA approval of abaloparatide. The abaloparatide sequence shares the first 20 N-terminal amino acids in common with PTHrP, but approximately half of the remaining amino acids are modified to ensure predominantly anabolic properties [44,143].…”
Section: Proteolytic Control Of Pthrp Functionmentioning
confidence: 99%
“…The molecular mechanisms by which abaloparatide exerts its effects on bone are not fully understood but may be related to the conformation-selective binding of the PTH1 receptor relative to other ligands including PTH and PTHrP [ 6 - 9 ]. Despite sharing some sequence homology, each hormone (PTH and PTHrP) plays a distinct role in bone physiology.…”
Section: Reviewmentioning
confidence: 99%
“…While both hormones act on the same receptor, recent studies have shown that continuous PTHrP administration stimulates bone formation preferentially, whereas continuous administration of PTH leads to more bone resorption than formation [ 6 , 9 ]. Both abaloparatide and teriparatide showed an increased messenger ribonucleic acid (RNA) expression level for the receptor activator of nuclear factor kappa-B ligand (RANKL) and macrophage colony-stimulating factor in a human osteoblastic cell line; however, these effects were rapidly reversed after the removal of abaloparatide from the culture media, while the effects were sustained in the teriparatide-treated cells [ 6 , 9 ]. Thus, PTHrP may cause transient stimulation of osteoblast cAMP production, which may result in lower osteoblast-derived RANKL expression and, therefore, less stimulation of bone resorption.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation